Green Poison from The Tropics: Annona muricata As Natural Insecticides Solution - Mei Ahyanti; Endah Setyaningrum; Prayudhy Yushananta (Jurnal Kesehatan, 2026)
The massive use of synthetic insecticides in vector and pest control has caused various problems, including insect resistance, environmental pollution, and the risk of toxicity to non-target organisms. Therefore, the development of natural insecticides based on tropical plants is becoming a more environmentally friendly and sustainable strategic alternative. One plant with potential as a bioinsecticide is Annona muricata (soursop). The method used is a systematic review study on scientific publications for the period 2020–2025 that report data on toxicity (LC₅₀), mortality, and safety against non-target organisms from various plant parts (seeds, leaves, and bark) against disease-vector insects, agricultural pests, and domestic insects. Data were analyzed descriptively to assess the effectiveness of insecticides based on plant parts, extract types, and target species. The review results show that Annona muricata has acetogenin with strong and broad-spectrum insecticidal activity. Insecticide activity has been reported against Spodoptera frugiperda, Plutella xylostella, Bactrocera sp., Periplaneta americana, Culex sp., Aedes albopictus, and Rhipicephalus spp., with mortality rates increasing as extract concentrations increase. Some studies have shown safe limits on non-target organisms at certain concentrations, indicating potential ecological selectivity. Formulation development, extract standardization, and advanced toxicity tests are still needed to optimize the application of Annona muricata-based bioinsecticides on a field scale.